The Remarkable Dual-Level Diversity of Prokaryotic Flagellins - Dalong Hu (American Society for Microbiology, 2020)
ABSTRACT Flagellin, the agent of prokaryotic flagellar motion, is very widely distributed and is the H antigen of serology. Flagellin molecules have a variable region that confers serotype specificity, encoded by the middle of the gene, and also conserved regions encoded by the two ends of the gene. We collected all available prokaryotic flagellin protein sequences and found the variable region diversity to be at two levels. In each species investigated, there are hypervariable region (HVR) forms without detectable homology in protein sequences between them. There is also considerable variation within HVR forms, indicating that some have been diverging for thousands of years and that interphylum horizontal gene transfers make a major contribution to the evolution of such atypical diversity. IMPORTANCE Bacterial and archaeal flagellins are remarkable in having a shared region with variation in housekeeping proteins and a region with extreme diversity, perhaps greater than for any other protein. Analysis of the 113,285 available full-gene sequences of flagellin genes from published bacterial and archaeal sequences revealed the nature and enormous extent of flagellin diversity. There were 35,898 unique amino acid sequences that were resolved into 187 clusters. Analysis of the Escherichia coli and Salmonella enterica flagellins revealed that the variation occurs at two levels. The first is the division of the variable regions into sequence forms that are so divergent that there is no meaningful alignment even within species, and these corresponded to the E. coli or S. enterica H-antigen groups. The second level is variation within these groups, which is extensive in both species. Shared sequence would allow PCR of the variable regions and thus strain-level analysis of microbiome DNA.